Unilateral Acts of a State in the Process of Forming Customary International Law - Kolasa, Jan (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Regardless of how broad acceptance within the academic community is for the formula that domestic legislation is acknowledged in international law as merely a fact, nearly equally prevalent is the conviction that the unilateral acts of states can be the basis for the creation of customary norms of international law. They can initiate and reinforce a practice constituting one of the two primary elements comprising the creation of a customary norm. They therefore do not constitute in and of themselves such a basis, but a certain practice has arisen in conjunction with them. They must be implemented. In any case, law-making practice can arise and establish itself without any written act or verbal declaration. It can simply be the result of the behaviour of states – their acts and omissions.
Keywords: unilateral acts of a State; customary international law; law-making process